NOTES ON RESUPINATE HYMENOMYCETES - II* The tulasnelloid fungi - M. A. DONK (BRIN Publishing (Penerbit BRIN), 1956)
1. Discussed are the tulasnelloid fungi, i.e. Tulasnella and other groups considered related by the author and also possessing spores capable of exhibiting repetition and not becoming septate. 2. The author rejects the designation epibasidia and considers the sterigmata in Tulasnella and Gloeotulasnella as being merely strongly inflated, a view already widely accepted. 3. He rejects the families Tulasnellaceae and Ceratobasidiaceae and includes them and the other tulasnelloid fungi in the Corticiaceae, which is still a heterogeneous group. Possible relations with other families are discussed.